Qualidade fisiológica de sementes de arroz irrigado armazenadas por dez anos em diferentes temperaturas - Krüger, Fabíola de Oliveira (2013)
Seed storage is an essential stage to maintain physical, physiological and sanitary quality of the seeds. However, for a long-term storage, it is necessary to keep the seeds respiratory activity at low levels, by reducing room temperature and moisture content, in order to slow of the deterioration process. Therefore, this research aimed to evaluate the physiological quality of rice seeds stored for ten years at different temperatures. We used seeds of the cultivars BRS Pelota, BRS Atalanta e BRS Firmeza stored for ten years at -15, 1 e 18 ºC. After storage, the seeds were evaluated for moisture, germination, germination first count, modified cold test, seedling emergence in greenhouse, index of emergence speed, length and dry weight of shoots and roots of seedlings from germination and emergence tests, antioxidant enzymes activity and respiratory activity. The tests results for viability and vigor showed temperatures at -15 and 1°C as the best temperatures for maintaining the physiological quality of seeds, and these results are consistent with the enzymatic activity. The lowest enzyme activities of the anti-oxidative defense system were detected in seeds stored at the temperatures that allowed a better preservation of their physiological potential. The seeds respiratory activity presented a relation with the vigor of seeds stored at different temperatures. According to the obtained results, we concluded that rice seeds of cultivars BRS Pelota, Atalanta BRS and BRS Firmeza maintain viability and vigor after ten years of storage at -15 and 1º C.